All-optical measurements of elastic constants in nematic liquid crystals - Klus, Bartłomiej W; Bajdecki, Waldemar K; Karpierz, Mirosław A (Photonics Letters of Poland, 2012)
Reorientation of liquid crystals induced by light is used as a method to measure elastic constants. Especially this all-optical method can determine constant connected with twist deformation, which is not easy in conventionally known methods. Experimental results show very good accuracy in comparison with other methods. Full Text: PDF References: T. Wu, "Birefringence dispersions of liquid crystals", Phys. Rev. A, 33 1270 (1986).CrossRef J. Kędzierski, Z. Raszewski, J. Rutkowska, T. Opara, J. Zieliński, J. Żmija, R. Dąbrowski, "Optical Investigation of the Vector Field of Directors in the L. C. Boundaried Nematic Medium Under Electric and Magnetic Fields", Mol. Cryst. Liq. Cryst. 249, 199 (1994).CrossRef W.K. Bajdecki, M.A. Karpierz, "Nonlinear Optical Measurements of Elastic Constants in Nematic Liquid Crystals", Acta Phys. Pol. A 95, 793(1999).DirectLink L. Calero, W.K. Bajdecki, R. Meucci, "Reorientation effect induced by a CW CO2 laser in nematic liquid crystal", Opt. Comun. 168, 201 (1999).CrossRef I.-Ch. Khoo,S. T. Wu, Optics and Nonlinear Optics of Liquid Crystals (Singapore, World Scientific Publ. 1993). DirectLink Liquid crystals databas, LiqCryst 4.2, © 2002 Volkmar Vill. A. Piccardi, M. Trotta, M. Kwaśny, A. Alberucci, R. Asquini, M. Karpierz, A. d’Alessandro, G. Assanto, "Trends and trade-offs in nematicon propagation", Appl Phys B 104, 805 (2011).CrossRef Experiments done by U.A. Laudyn, M. Kwaśny and M.A. Karpierz. U.A. Laudyn, K. Jaworowicz, M.A. Karpierz, "Blue to deep UV light emission from a p-Si/AlN/Au heterostructure", Appl. Phys. Lett. 94, 091110 (2009).CrossRef